Total saponins from Trillium tschonoskii Maxim promote neurological recovery in model rats with post-stroke cognitive impairment - Wang, Gang; Tang, Xiane; Zhao, Fangyu; Qin, Xiaoli; Wang, Fengjie; Yang, Dan; Zhu, Hong; Chen, Xianbing (Frontiers in Pharmacology, 2023)
Total saponin from Trillium tschonoskii Maxim (TSTT), a bioactive component of local natural herbs in Enshi area, China, has demonstrated to have functions of restoring cognitive capacity and promoting axonal regeneration post-stroke, but the mechanism of this process remains unclear. The hippocampus is a critical tissue for controlling learning and memory capacity, and the sonic hedgehog (Shh) signaling pathway plays a major role in the patterning and synaptic plasticity of hippocampal neural circuits.an important role in the formation and plasticity of neuronal circuits in the hippocampus.Therefore, we aimed to investigate whether TSTT could restore learning and cognitive functions by modulating the Shh signaling pathway in rats with poststroke cognitive impairment (PSCI). The ischemia model was established by permanent middle cerebral artery occlusion (MCAO) in 100 Sprague-Dawley (SD) rats and the model rats were administered with TSTT (100 mg/kg) or donepezil hydrochloride as the positive control (daily 0.45 mg/kg, DON) for four weeks after the operation. As assessed by the Morris water maze, the cognitive function of PSCI rats was significantly improved upon TSTT treatment. Meanwhile, cerebral infarct volume reduced with TSTTTSTT reduced the volume of cerebral infarction as shown by HE and TTC staining, and significantly increased the number of Nissl bodies and dendritic spine density as shown by Nissl and Golgi staining. In addition, TSTT upregulated and